Transferencia de tecnología universidad-industria en las universidades públicas estatales de México: un análisis cualitativo comparado - Calderón Altamirano, Elisa (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The purpose of this research is to identify the necessary and sufficient conditions that generate high performance in the university-industry technology transfer processes in the State Public Universities of Mexico (UPEs). Some approaches are presented on the background of the role of universities in the new knowledge economy, general considerations and public policy approaches in science, technology and innovation, and models of university-industry technology transfer are presented in the global context. The research uses the comparative qualitative analysis (fsQCA) approach to learn about the necessary and sufficient conditions, and their possible configurations to achieve a high level of performance. The results obtained show four configurations that lead to the desired result. An aspect that should be highlighted in this research are the five conditions, of which four are considered necessary to generate high performance: institutional capacity, entrepreneurship capacity, academic capacity and academic competitiveness. Regarding the capacity for innovative development, the results suggest that this condition is not necessary for high performance. This may be due to the fact that most of the research that is carried out is basic research, and because there is no culture regarding the generation of products or knowledge that can be protected through intellectual property.

La presente investigación tiene el propósito de identificar las condiciones necesarias y suficientes que generan un alto desempeño en los procesos de transferencia de tecnología universidad-industria en las Universidades Públicas Estatales de México (UPEs). Se presentan algunos planteamientos sobre los antecedentes del papel de las universidades en la nueva economía del conocimiento, consideraciones generales y los enfoques de política pública en ciencia, tecnología e innovación y se exponen los modelos de transferencia de tecnología universidad-industria en el contexto global. La investigación utiliza el enfoque de análisis cualitativo comparado (fsQCA) para conocer sobre las condiciones necesarias y suficientes, y sus posibles configuraciones para alcanzar un alto nivel de desempeño. Los resultados obtenidos muestran cuatro configuraciones que llevan al resultado deseado. Un aspecto que se debe resaltar en esta investigación son las cinco condiciones, de las cuales cuatro son consideradas necesarias para generar un alto desempeño: capacidad institucional, la capacidad de emprendimiento, la capacidad académica y la competitividad académica. Respecto de la capacidad para el desarrollo innovador, los resultados sugieren que esta condición no es necesaria para un alto desempeño. Esto puede deberse a que la mayoría de la investigación que se realiza es básica, y a que no existe una cultura en cuanto a la generación de productos o conocimientos susceptibles de ser protegidos a través de la propiedad intelectual.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-D-2022-1506; Transferencia de tecnología; Universidad-industria; Análisis cualitativo comparado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8374